Metas de socialização e práticas parentais em famílias com diferente número de filhos - Carlos, Karla Alves (2012)
The socialization goals and educational practices used by parents have an important influence on interactions that are established and consequently on child development. The objective of this study is to investigate the Socialization s Goals and Parental Educational Practices in families with one child and families with two or three children. The study included 41 mothers of medium socio-economic status, married or cohabiting, with at least secondary education, with one or two or three children, living in the city of João Pessoa. We applied a semi-structured interview related to Socialization s Goals, a Parental Practices Inventory and a questionnaire for socio-demographic characteristics. The data were treated to compare the results of both groups of mothers and highlighted the importance of educational level of the mother to offspring education provided. The results showed there is no statistically significant difference between the two groups of mothers who have lower average among mothers with one child and two and three children in the instrument of parental practices in social involvement and responsibility. In an interview about socialization goals the difference was indicated by the higher frequency sub-group of only-child mother related to social aspects and responsibilities of parents towards their children. It is emphasized that, despite the literature pointing out that the father is more involved, it is still attributed to the mother most of the responsibility and reference for the children s education. The influences for their children's education are independent of family size and do not occur unilaterally, being influenced by the child s birth order, gender, personality, age, and other characteristics as well as support networks for children care, such as grandparents. Thus the attitudes and educational decisions are made individually for each child, regardless of the number of children.